Hazard analysis on public private partnership projects in developing asia. - Minso,Lee (Manila Asian Development Bank, 2018)
The cancellation of public private partnership projects discourages private investment and interrupts the delivery of infrastructure and services. Developing Asia accounts for more than half of all PPP projects cancelled globally. This study uses a hazard regression analysis to show that project survival is more assured with government support through subsidies and guarantees, and strategies for proper planning, preparation, and implementation. Furthermore, robust economic growth, an improved legal and institutional environment, the existence of a dedicated PPP unit, and the involvement of multilateral development banks leads to good project outcomes.
Keywords: Public-private sector cooperation; Public-private sector collaboration; Electronic books